2008
DOI: 10.1111/j.1438-8677.2008.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of essential oil glands of clary sage (Salvia sclarea L., Lamiaceae)

Abstract: The Lamiaceae is rich in aromatic plant species. Most of these species produce and store essential oils in specialised epidermal oil glands, which are responsible for their specific flavour. Two types of glands producing essential oil and possessing different morphological structure can be found in Salvia sclarea: peltate and capitate glands. The content of single oil glands from different positions on the plant (corolla, calyx and leaf) were sampled using an SPME fibre and analysed by gas chromatography in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 21 publications
5
47
1
Order By: Relevance
“…Indeed, Pichersky et al (2006) mentioned that free volatiles are glycosylated and stored in cell vacuoles to likely increase cellular swelling and thus to contribute to decrease the effect of osmotic stress inherent to salinity. While the oil yield decrease observed at NaCl concentrations of 50 and 75 mM may be explained by salt-induced necrosis observed in leaves, these organs possess two types of glands producing essential oil: peltate and capitate glands which constitute the main sites of essential oil secretion and accumulation in clary sage (Schmiderer et al 2008). The observed necrosis of the extremity of most leaves at 50 mM and particularly at 75 mM NaCl could have led to the degradation of some oil glands of leaves and thus to the decrease in oil yield.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Pichersky et al (2006) mentioned that free volatiles are glycosylated and stored in cell vacuoles to likely increase cellular swelling and thus to contribute to decrease the effect of osmotic stress inherent to salinity. While the oil yield decrease observed at NaCl concentrations of 50 and 75 mM may be explained by salt-induced necrosis observed in leaves, these organs possess two types of glands producing essential oil: peltate and capitate glands which constitute the main sites of essential oil secretion and accumulation in clary sage (Schmiderer et al 2008). The observed necrosis of the extremity of most leaves at 50 mM and particularly at 75 mM NaCl could have led to the degradation of some oil glands of leaves and thus to the decrease in oil yield.…”
Section: Discussionmentioning
confidence: 99%
“…Hose et al (1997) also showed that the composition in essential oil glands of M. officinalis changes during ontogenesis. This is mentioned for other species (Salvia sclarea L., Satureja hortensis L., Salvia officinalis L.) as well (Grassi et al 2004;Johnson et al 2004;Novak et al 2006;Schmiderer et al 2008).…”
Section: Composition Of Essential Oilmentioning
confidence: 97%
“…hirtum, polymorphism could be detected, even within one individual plant, between different oil glands of a single leaf (Johnson et al, 2004). However, this kind of polymorphism is not very usual, being the difference in the oil composition between glands usually related to gland age (Grassi et al, 2004;Johnson et al, 2004;Schmiderer et al, 2008). In general, the different growth stages of the plant create variations in the oil composition within the same organ of the plant (Chamorro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%